Study Retrospektif Kejadian Stunting Pada Balita - Wa Ode Salma; La Ode Alifariki; Heriviyatno J Siagian (STIKes Payung Negeri Pekanbaru, 2022)
Stunting is one of the nutritional problems that occurs in the world, especially in poor and developing countries, including Indonesia. Stunting can also be used as an indicator of child growth indicating chronic malnutrition. This study aims to analyze the predictors of stunting based on aspects of antenatal care and postnatal care. This research is a quantitative analytic study with a case-control study approach involving 90 mothers with children aged 24-59 months who live in the coastal area of ​​Kolaka Regency. The data was processed using the SPSS application, and tested with the Odds Ratio (OR) test. If the LL-UL value does not contain a value of 1, it is considered significant. The predictor/independent variable showed that the risk factor for the history of zinc supplementation on the incidence had an OR value of 9,846 (3.717-26,083). This means that toddlers who consume zinc irregularly have a risk of 9.8 suffering from stunting. The risk factor for a history of helminthiasis on stunting has an OR value of 7.608 (2.981-19,4176,089), meaning that toddlers who have a history of worms are at risk of 7.6 times suffering from stunting. The risk factor for a history of exclusive breastfeeding for stunting has an OR value of 4.984 (2.028-12.253), meaning that toddlers who receive exclusive breastfeeding for less than 6 months have a 4.9 times risk of suffering from stunting. The incidence of stunting in toddlers in Kolaka Regency is influenced by exclusive breastfeeding, history of worms, history of zinc supplementation.